2005
DOI: 10.2201/nonlin.003.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response—A Challenge for Allelopathy?

Abstract: The response of an organism to a chemical depends, among other things, on the dose. Nonlinear dose-response relationships occur across a broad range of research fields, and are a well established tool to describe the basic mechanisms of phytotoxicity. The responses of plants to allelochemicals as biosynthesized phytotoxins, relate as well to nonlinearity and, thus, allelopathic effects can be adequately quantified by nonlinear mathematical modeling. The current paper applies the concept of nonlinearity to asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 56 publications
0
53
0
Order By: Relevance
“…Examples of hormesis (the stimulation effect of a toxin at low doses) with natural phytotoxins have been reported with single compounds (e.g., gramine and hordenine, benzoxazolin-2(3H)-one, and allyl isothiocyanate), plant extracts (e.g., Triticum aestivum L.), and root exudates (e.g., T. aestivum and Triticum spelta L.) (An et al 1993;Belz et al 2005Belz et al , 2007. Belz (2008) reported that hormetic effects might occur in a natural setting if doses released are low, and they should be regarded as a potential low dose component of plant/plant interference.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of hormesis (the stimulation effect of a toxin at low doses) with natural phytotoxins have been reported with single compounds (e.g., gramine and hordenine, benzoxazolin-2(3H)-one, and allyl isothiocyanate), plant extracts (e.g., Triticum aestivum L.), and root exudates (e.g., T. aestivum and Triticum spelta L.) (An et al 1993;Belz et al 2005Belz et al , 2007. Belz (2008) reported that hormetic effects might occur in a natural setting if doses released are low, and they should be regarded as a potential low dose component of plant/plant interference.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this feature excludes the application of an allelopathic compound as a selective herbicide or totally prohibits its usage in weed management. On the other hand, effects of allelopathins in acceptor plants are highly dose-dependent [13]. This allows the opportunity to search out compounds exhibiting selectivity.…”
Section: Advantages and Disadvantages Of Allelopathins As Bioherbicidesmentioning
confidence: 99%
“…All of this is predicated in the assumption that chemical signals and/or competition from the receiving plant species do not influence allelochemical production of the donor species (see discussion above). The results of this type of experiment can also be complicated by hormesis (stimulatory effect of a subtoxic dose of a toxin) effects at low densities of the donor species (Belz et al 2005). Sampling time can also influence the results, so, ideally, several sampling times should be designed into the experiment.…”
Section: Preliminary Studies That Can Indicate Allelopathymentioning
confidence: 99%
“…Some allelochemicals, such as sorgoleone (Dayan et al 2010;Weston et al 2013), m-tyrosine (Bertin et al 2007), and scopoletin (Belz et al 2005) are exuded by roots, and, as in the case of sorgoleone, may be exuded or secreted into the soil almost as quickly as they are produced. Furthermore, soil microbes can convert less-phytotoxic root exudates to more phytotoxic compounds, making the discovery of the true ''allelochemical'' even more difficult.…”
Section: Finding the Allelochemicalsmentioning
confidence: 99%
See 1 more Smart Citation